Modeling aqueous humor collection from the human eye - Kapnisis, Konstantinos; Doormaal, Mark Van; Ross Ethier, C. (My University, 2009)
Glaucoma is a common cause of blindness. Studies of this disease can involve collection of aqueous humor (AH) fluid from eyes of patients undergoing surgery, which involves aspirating a small fluid volume from the anterior region of the eye through a fine-bore needle. Unfortunately, the composition of the AH is spatially non-uniform in the eye, and thus the composition of the aspirated fluid is uncertain. Our goal was to numerically simulate the AH aspiration process to determine where the aspirated fluid was being collected from and thus gain insight into the composition of the collected fluid. A 3D computational model of the anterior region of the human eye was created and the Navier-Stokes equations were numerically solved during the aspiration process for a set of typical (baseline) conditions: 40 μl aspirated volume and needle placement in the central anterior chamber. We also ran variations of this baseline simulation. The main finding was that the aspirated fluid comes from a very localized region around the needle tip, so that for typical conditions, almost no aspirated fluid is withdrawn from the angle region of the anterior chamber. This is important because the AH in this angle region is protein-rich and directly interacts with the tissues that control fluid drainage from the eye. Recommendations for standardizing aspiration conditions are given.
Keywords: Glaucoma; Anterior chamber; Posterior chamber; Aqueous humor fluid; Drainage angle; Navier–Stokes equations; Finite elements